2003
DOI: 10.1038/sj.npp.1300229
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Magnetic Seizure Therapy (MST) in Major Depression: Randomized Within-Subject Comparison with Electroconvulsive Therapy

Abstract: Magnetic seizure therapy (MST) is a novel means of performing convulsive therapy using rapidly alternating strong magnetic fields. MST offers greater control of intracerebral current intensity than is possible with electroconvulsive therapy (ECT). These features may result in a superior cognitive side effect profile for MST, while possibly retaining the efficacy of ECT. The objective of this study was to determine whether MST and ECT differ in seizure characteristics, and acute objective and subjective cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
173
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 242 publications
(188 citation statements)
references
References 82 publications
7
173
0
8
Order By: Relevance
“…In MST, which has fewer cognitive side effects, focal seizure activity is induced by TMS (Lisanby, Luber, Schlaepfer, & Sackeim, 2003). In a small open label pilot clinical trial (N=13), 38,5 % of the depressed patients showed clinical response at the end of the study (Fitzgerald et al, 2013).…”
Section: Neurostimulation Approaches To Treatment Resistancementioning
confidence: 99%
“…In MST, which has fewer cognitive side effects, focal seizure activity is induced by TMS (Lisanby, Luber, Schlaepfer, & Sackeim, 2003). In a small open label pilot clinical trial (N=13), 38,5 % of the depressed patients showed clinical response at the end of the study (Fitzgerald et al, 2013).…”
Section: Neurostimulation Approaches To Treatment Resistancementioning
confidence: 99%
“…12,116 These findings support the hypothesis that it is an imbalance within these circuits, rather than any specific directional disturbance in a sin- gle region, that provides a neural substrate for mood dysregulation. Magnetic seizure therapy (MST), an experimental technique using a magnetic field to induce a seizure, is currently being investigated in the treatment of depression by Lisanby et al 117 They have reported some preliminary evidence that MST may have fewer cognitive side effects than ECT. They further hypothesize that, based on intracerebral electrode studies in nonhuman primates and the fact that magnetic fields are not impeded by skull and soft tissues as is electricity, MST (if proven effective) may represent an improvement over ECT as the seizure can be more directly targeted at affective circuits and therefore may have fewer cognitive side effects than ECT.…”
Section: Presumptive Mood Disorder Circuitsmentioning
confidence: 99%
“…This study reported low cognitive side effects in both ECT and MST groups, with faster reorientation following MST. In addition to faster reorientation, Lisanby et al (2003a) found significantly superior acute cognitive performance after MST than ECT. Faster reorientation after MST compared with prior ECT treatments was reported as well (Kirov et al, 2008).…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, magnetic seizure therapy (MST) elicits generalized seizures with an induced electric field that is substantially less intense and more focal than conventional ECT (Deng et al, 2011(Deng et al, , 2013Lee et al, 2014). After a series of promising case reports and safety and feasibility assessments (Kayser et al, 2009;Kosel et al, 2003;Lisanby et al, 2003aLisanby et al, , 2001, the efficacy and side effects of MST were evaluated in two larger studies of 13 patients (Fitzgerald et al, 2013) and 26 patients (Kayser et al, 2015). In these studies, the response rates were 38% and 69%, and the remission rates were 15% and 46%, respectively.…”
Section: Introductionmentioning
confidence: 99%